Voices of Didactics: Transgenerational paths of researchers in the University of Aveiro - Lourenço-Simões, Carolina (2023)
We live in a constantly changing world. Those transformations, which echo in Education, span several generations of researchers, and have led to an epistemological and praxeological reconfiguration of Didactics towards a hermeneutic character. Considering this panorama, we sought to answer the following questions: (1) What is the perception of different generations of researchers from the University of Aveiro concerning Didactics? and (2) How has the perception of the concept of Didactics been built by those researchers throughout their personal and professional life paths? To this end, the following aims were outlined: (i) to understand the personal and professional paths of the participants; (ii) to characterize their perception of the concept of Didactics; and (iii) to analyze their epistemological perspectives regarding the topic. Data research was carried out through standardized open-ended interviews with nine researchers of the University of Aveiro specialized in the field of Didactics and from different generations. With the support of the webQDA software, we proceeded to a categorical data analysis. The results demonstrate that the researchers have a similar conception of Didactics and highlight the existence of a school of thought that defines the institutional identity of the University of Aveiro in this field, but denote, as well, idiosyncrasies, which emerge from the individual paths and from the different generational contexts of the researchers.